Effect of Nd3+, Pectin and Poly(ethylene glycol) on the Photocatalytic Activity of TiO2/SiO2 Film - Aberoom, Parviz; Moradi Dehaghi, Shahram; Samadi, Susan; Kamyar, Shabnam; Saber Tehrani, Mohammad (Asian Journal of Chemistry, 2010)
Titanium dioxide/silicon dioxide films were prepared by the sol-gel method without and with Nd3+ as a dopant, pectin and poly(ethylene glycol) as an additive. Scanning electron microscopy (SEM) has showed that the particle size of Nd-TiO2/SiO2 with pectin is smaller than poly(ethylene glycol) and the microstructure of the films have become loose with the addition of pectin. The influence of Nd3+, pectin and poly(ethylene glycol) on the phase transformation of TiO2/SiO2 films from amorphous to anatase has been investigated by using X-ray diffraction. Films photocatalytic activities have been evaluated by a UV- exposure test. The results showed that the selfcleaning of nanocomposite Nd-TiO2/SiO2 was enhanced by organic polymer, especially pectin.